The the effects of region original revenue, general fund allocation, specific fund allocation, capital expenditure to economic growth in West Borneo Province - Monica Olivia (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research aims to examine the effects of region original revenue, general fund allocation, specific fund allocation, capital expenditure to economic growth. The population in this study were 12 counties and 2 city in West Borneo Province during the period of 2016 – 2018. The data used in this research is secondary data obtained from the document of Badan Pusat Statistik of West Borneo Province on official website https://kalbar.bps.go.id. The analytical method used multiple linear regression analysis with a significance level of 5% and help of SPSS version 20. The results show in partially that specific fund allocation has negative significant effects on the economic growth; but region original revenue, general fund allocation and capital expenditure has no effects on the economic growth in West Borneo Province. While in simultaneously the fourth variables has no effects on the economic growth in West Borneo Province.